Lower gefitinib dose led to earlier resistance acquisition before emergence of T790M mutation in epidermal growth factor receptor‐mutated lung cancer model - Hayakawa, Hiromi (Cancer Sci, 2013)
Non‐small‐cell lung cancers with epidermal growth factor receptor (EGFR) mutations are sensitive to EGFR tyrosine kinase inhibitors (TKIs); however, unlike cytotoxic agents, it is generally accepted that minimal doses of drugs inhibiting target molecules are sufficient when molecular‐targeted agents, including EGFR‐TKIs, are used. Thus, any utility of higher doses remains unclear. We compared low‐dose (15 mg/kg) gefitinib therapy with high‐dose (50 mg/kg) therapy using an EGFR‐mutated lung cancer xenograft model. Both gefitinib doses induced tumor shrinkage, but tumors regrew in the low‐dose group within 1 month, whereas tumors in the high‐dose group did not. Neither the T790M mutation nor MET amplification was apparent in regrown tumors. We also compared outcomes after two doses of gefitinib (5 and 25 mg/kg) in a transgenic EGFR‐mutated lung cancer mouse model. In line with the results obtained using the xenograft model, both gefitinib doses completely inhibited tumor growth, but tumors treated with the lower dose of gefitinib developed earlier drug resistance. In conclusion, a low gefitinib dose caused tumors to become drug‐resistant prior to acquisition of the T790M mutation or MET amplification in EGFR‐mutated models of lung cancer. This suggests that it is important to optimize the EGFR‐TKI dose for treatment of EGFR mutation‐associated lung cancer. Gefitinib may need to be given at a dose greater than the minimum required for inhibition of target molecules.